NFAT Gene Family in Inflammation and Cancer - Pan, M.-G.; Xiong, Y.; Chen, F. (Current Molecular Medicine, 2013)
Calcineurin-NFAT signaling is critical for numerous aspects of vertebrate function during and after embryonic development. Initially discovered in T cells, the NFAT gene family, consisting of five members, regulates immune system, inflammatory response, angiogenesis, cardiac valve formation, myocardial development, axonal guidance, skeletal muscle development, bone homeostasis, development and metastasis of cancer, and many other biological processes. In this review we will focus on the NFAT literature relevant to the two closely related pathological systems: inflammation and cancer.
Keywords: NFAT